The musicalization of graphic narratives and P. Craig Russell's graphic novel operas, The Magic Flute and Salomé. Issue 1 (1st July 2017) - Addis, Victoria
The term 'musicalization' comes from Werner Wolf's study of intermediality between music and fiction, The Musicalization of Fiction (1999), which proposes the musicalized text as one that has an intentional and sustained connection to music and musical form that moves beyond the purely diegetic or incidental. In this article I draw on Wolf's arguments to consider the potential for 'musicalization' within graphic narratives, interrogating comics both as a unique medium, and through a comparative analysis with the operations of time, space, rhythm, repetition, harmony, dissonance, polyphony, and narrativity in music. I explore these ideas further in a close analysis of two of P. Craig Russell's graphic novel operas, The Magic Flute (1989–90) and Salomé (1986), which I present as tentative examples of musicalized graphic narratives. These graphic novel operas draw on the affinities that we find between music and comics to translate their musical source texts into graphic narratives through the use of medium specific tools, e.g. manipulations of the panel and the grid, visual approximations of sound, and grammatextuality. This research highlights a long-standing desire among comic writers and artists to represent music in their work, and demonstrates the rich connections between music and graphic narratives, which can facilitate more nuanced representations moving forward.